2018
DOI: 10.22146/jpti.24806
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Turnera subulata and Cosmos sulphureus Flowers in the Life of Anagrus nilaparvatae (Hymenoptera: Mymaridae)

Abstract: Anagrus nilaparvatae is a potential egg parasitoid to control the rice brown planthopper (Nilaparvata lugens Stal.) The parasitoid needs to consume suitable food to maximize its biotic potential and parasitizing ability. This study was aimed to determine the benefits provided by the presence of Turnera subulata and Cosmos sulphureus flowers on the life of A. nilaparvatae. This study consisted of two experiments. The first experiment was designed to determine the effects of the tested flowers on the parasitism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Flowers's pollen and nectar which contains sugar, protein, amino acids, and lipids, could increase the fecundity of parasitoids (Vattala et al., 2006). Many studies reported increased longevity using honey or flowers as the food sources, compared with water or no food did not significantly extend the longevity of parasitoids (Mitsunaga et al., 2006; Winkler et al., 2009; Sugiharti et al., 2018), while carbohydrates are also a nutritional factor determining the longevity of parasitoid wasps. Leatemia et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flowers's pollen and nectar which contains sugar, protein, amino acids, and lipids, could increase the fecundity of parasitoids (Vattala et al., 2006). Many studies reported increased longevity using honey or flowers as the food sources, compared with water or no food did not significantly extend the longevity of parasitoids (Mitsunaga et al., 2006; Winkler et al., 2009; Sugiharti et al., 2018), while carbohydrates are also a nutritional factor determining the longevity of parasitoid wasps. Leatemia et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, information on maintaining C. vestalis populations in the field by applying ecological engineering to provide plant-derived foods of pollen and nectar which greatly influence natural enemy longevity, fecundity, and behavior and positively impact on reducing Plutella xylostella (L.) numbers is lacking (Mitsunaga et al., 2006). Many flowers have been intensively studied to determine the effects of floral nectar on longevity of Microctonus hyperodae Loan including phacelia ( Phacelia tanacetifolia ), buckwheat ( Fagopyrum esculentum ), alyssum ( Lobularia maritima ), coriander ( Coriandrum sativum ), white clover ( Trifolium repens ), red clover ( Trifolium pratense ) and white mustard ( Sinapis alba ) (Vattala et al., 2006), on longevity of Cotesia as Centaurea cyannus L., C. jacea L., Origanum vulgare L., and Trifolium pratense L (Winkler et al., 2009), and on longevity of the Anagrus nilaparvatae parasitoid as Turnera subulata and Cosmos sulphureus (Sugiharti et al., 2018). Moreover, select plant species that provide nutritional benefits to the parasitoid play an important role when designing field margins.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the presence of refuge can increase the number of natural enemies by 72% and reduce the number of pest populations by 74% (Letourneau et al, 2011). According to Sugiharti et al (2018), the flowers of Turnera subulata and Cosmos sulphureus provided for A. nilaparvatae adults increased the fecundity of their offsprings by 45-91%.…”
Section: Introductionmentioning
confidence: 99%
“…. Beberapa penelitian melaporkan peran C. sulphureus sebagai biopestisida (Sugiharti et al, 2018;Rezki et al, 2018, Imaniar et al, 2013 (1) Keterangan:…”
Section: Pendahuluanunclassified